Two‐year follow‐up of patients with septic shock presenting with low HDL: the effect upon acute kidney injury, death and estimated glomerular filtration rate. (19th March 2017) - Roveran Genga, K.; Lo, C.; Cirstea, M.; Zhou, G.; Walley, K. R.; Russell, J. A.; Levin, A.; Boyd, J. H.
Abstract: Background: Sepsis is associated with decreased levels of high‐density lipoprotein (HDL) cholesterol. HDL has anti‐inflammatory properties, and the use of Apo A‐I mimetic peptides is associated with renal function improvement in animal models of sepsis. However, it is not known whether decreased HDL level results in impaired renal function in human sepsis. We investigated whether low levels of HDL conferred an increased risk of sepsis‐associated acute kidney injury (AKI) or long‐term decreased estimated glomerular filtration rate (eGFR) after sepsis. Methods: HDL concentration (mg dL −1 ) was measured in plasma samples from 180 patients with septic shock at admission to the Emergency Department (ED). We divided the patients using median HDL as a cut‐off value and assessed the frequency of sepsis‐associated AKI and long‐term decreased eGFR after sepsis. Univariate and multivariate analyses were performed. Results: Patients with low HDL had a significantly greater frequency of KDIGO 2 or 3 sepsis‐associated AKI [39/90 (43.3%) vs. 12/90 (13.3%), P < 0.001] and decreased long‐term eGFR [24/58 (41.4%) vs. 11/57 (19.3%), P = 0.018] compared to those with high HDL. The adjusted OR for sepsis‐associated AKI and decreased eGFR after sepsis in the lower HDL group was 2.80 (95% CI 1.08–7.25, P = 0.033) and 5.45 (95% CI 1.57–18.93, P = 0.008), respectively. Conclusion: Low HDL levels during sepsis are associated with increased risk of sepsis‐associated AKI, and/or subsequent decreased eGFR. These results suggest that HDL may be involved and/or may be a marker of kidney injury during and after sepsis.